Optimalisasi Penggunaan Media Sosial dalam Promosi Pariwisata Pulau Untung Jawa - Lasmery RM Girsang; Ilona V.O Situmeang; William Althur (Jurnal Karya untuk Masyarakat (JKuM), 2025)
Not all tourist destinations in the Seribu Islands are considered having no obstacles. Among various islands, one of them is Untung Jawa Island which still improves. In fact, the condition of tourist destinations on Untung Jawa Island has kept great potency but has not been managed optimally yet. This was caused by some factors, one of them was less promotion effort carried out by tour guides on the island. Therefore, on December 17, 2024, the community service team conducted sharing and training for participants from "Puja Berhias" members. The community service activities were filled with providing materials related to increasing the effectiveness of tourism promotion through content by relying on storytelling techniques. From the results of the activity, the participants were able to re-explore the narrative of promotional content social media. From simple content at the beginning, it has now become more creative content and has selling value. Hopefully, the community service activities can sharpen the knowledge and skill of the community of Untung Jawa Island.